2019
DOI: 10.1038/s41467-019-08830-w
|View full text |Cite
|
Sign up to set email alerts
|

High performance planar germanium-on-silicon single-photon avalanche diode detectors

Abstract: Single-photon detection has emerged as a method of choice for ultra-sensitive measurements of picosecond optical transients. In the short-wave infrared, semiconductor-based single-photon detectors typically exhibit relatively poor performance compared with all-silicon devices operating at shorter wavelengths. Here we show a new generation of planar germanium-on-silicon (Ge-on-Si) single-photon avalanche diode (SPAD) detectors for short-wave infrared operation. This planar geometry has enabled a significant ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 52 publications
2
115
1
1
Order By: Relevance
“…Detectors based on superconducting nanowires, such as the one shown in Figure 7c-e, similarly operate at cryogenic temperatures only. Recent waveguidecoupled Ge-on-Si avalanche photodiodes showed that single photon detection in room temperature conditions was possible [107]; a similar Ge-on-Si photodiode with a different design showed a detection efficiency of 38% at 125 K [108].…”
Section: Single Photon Detectorsmentioning
confidence: 99%
“…Detectors based on superconducting nanowires, such as the one shown in Figure 7c-e, similarly operate at cryogenic temperatures only. Recent waveguidecoupled Ge-on-Si avalanche photodiodes showed that single photon detection in room temperature conditions was possible [107]; a similar Ge-on-Si photodiode with a different design showed a detection efficiency of 38% at 125 K [108].…”
Section: Single Photon Detectorsmentioning
confidence: 99%
“…Although they realize near-ideal detection, a cryogenic temperature is required [ 30 , 31 ], making them unsuitable for full integration on chip. Recently, single photon avalanche detectors (SPADs) near room temperature have been demonstrated at 1330 nm and 1550 nm, using a vertically coupled Ge APD and a waveguide butt-coupled GeSn APD, respectively [ 43 , 44 ]. In the current state-of-the-art, their performances are limited by the dislocation density at the Si interface.…”
Section: Chip-integrated Parity-based Detection Techniquementioning
confidence: 99%
“…Typically, InGaAs/InP based SPADs exhibit single-photon detection efficiencies (SPDEs) ranging from 20 % to > 50 % in the SWIR and operate at Peltier-cooled temperatures between 220 K and 255 K [18][19][20][21][22][23] , this is advantageous because Peltier-cooling has less stringent requirements for size, weight and power consumption in comparison to cryogenic cooling, facilitating the development of compact detector modules. Another challenge associated with InGaAs based SPADs is that the achievable count rates are markedly restricted by prominent afterpulsing effects [24][25][26] , however, progress continues to be made in mitigating this issue 21,27 .…”
Section: Introductionmentioning
confidence: 99%